(untitled) (Journal of the College of Basic Education, 2022)
The commercial and economic relationships were characterized by progressing and developing distinctly between India and Iran during the reign of the Shah if it is compared to the neighboring countries in the region. India was importing crude oil and sulfur from Iran and exporting consumer and investment goods to Iran. At the beginning of 1974, a commercial agreement was signed between the two countries for the purpose of regulating export and import operations. The evidences indicate that the Shah of Iran had a strong desire to develop and strengthen commercial and economic cooperation with India in joint projects. It was agreed to invest about 650 million in the iron ore project (Code Ramanh). Indian companies have invested their money in many projects with Iranian investors, including a project for spare parts for cars, a joint venture for construction, another for the production of steel bars, and a project for spare parts for automatic cars, in addition to the Indian companies’ contribution to the implementation of many housing projects in Iran. For the Asian Common Market, the Shah of Iran tried to provide various aids, loans and grants to India in order to accept his call, but it failed. The Shah’s goal in establishing the market was to implement his political and economic goals in the region for his interests .The commercial and economic relationships between India and Iran during the republican era in 1979 were characterized by a kind of stagnation due to the cessation of Iranian oil pumping in that year and the failure to pay the rest of the financial installments to India. After the outbreak of the Iraq-Iran war, foodstuffs, medical supplies and other commodities began to arrive in Iran from India. This is done in return for exporting crude oil twice as much to India.India had made great efforts for the sake of strong commercial and economic relationships with Iran during the republican era, by sending frequent commercial and official delegations to Iran and signing various agreements and contracts. India is also trying to sign long-term contracts with Iran in order to supply it with crude oil, because of its geographical location and its proximity to India. Iran is also one of the most important suppliers of oil to India.In brief, we can confirm that India is based on its commercial and economic relations from its interest and aim to secure crude oil and its derivatives, due to the economic and social difficulties. India can enter into cooperation with Iran that affects national and national security if it is supplied with crude oil and the quantities it needs. This may not happen if the Arab countries supply India with crude oil, with the quantities it needs, and at prices slightly lower than those of OPEC. It is also possible to influence the Indian government by cooperating with Pakistan to raise the problem of the border areas and Kashmir. It is also possible to cooperate with Indian Muslims and Sikhs to put pressure on the Indian government.